Deteksi penyakit Brucellosis pada kerbau dengan metode Rose Bengal Test (RBT) di Balai Besar Veteriner Maros - Wahdaniyah, Wahdaniyah; Sijid, St. Aisyah; Wirawan, Hadi Purnama (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2024)
Brucellosis is an infectious disease caused by bacteria from the genus Brucella, which are intracellular microorganisms and zoonotic for both humans and animals. This study aims to detect the presence of Brucella abortus bacteria in buffalo blood serum samples. This type of research is descriptive and exploratory, detecting the presence of B. abortus bacteria in buffalo serum samples using the Rose Bengal Test (RBT) method. The results obtained showed that of the 80 samples tested, the results were negative for Brucellosis because there was no agglutination in the buffalo serum to which the RBT reagent was added. This indicates that there are no antibodies in the samples. In other words, the buffalo used are free from Brucella infection. However, to confirm these results, further tests such as the Complement Fixation Test (CFT) and the Enzyme-Linked Immunosorbent Assay (ELISA) are necessary.